Association between dietary carotenoid intakes and the risk of asthma in adults: a cross-sectional study of NHANES, 2007–2012 - Weijie Li; Wei Zhang; Jie Du (BMJ Open)
Objective To investigate the association between dietary carotenoid intake and asthma using data from a nationally representative sample of US adults.Design Cross-section study.Setting The National Health and Nutrition Examination Survey 2007–2012.Participants A total of 13 039 participants aged 20–80 years (current asthma n=1784, non-current asthma n=11 255) were included in this study.Primary and secondary outcome measures Asthma was defined by self-report questionnaires. Weighted logistic regression analyses and the smooth curve fittings were performed to explore the association between total carotenoid intake, dietary carotenoid subgenera, including (α-carotene, β-carotene, β-cryptoxanthin, lutein with zeaxanthin and lycopene) and the risk of asthma.Results The ORs with 95% CIs of dietary α-carotene, dietary β-carotene, dietary β-cryptoxanthin, total lutein with zeaxanthin, total lycopene, dietary carotenoid and total carotenoid intake for individuals with current asthma after adjusting the confounders in model 3 were 0.80 (0.67 to 0.95), 0.67 (0.57 to 0.79), 0.68 (0.55 to 0.85), 0.77 (0.61 to 0.98), 0.71 (0.57 to 0.87), 0.75 (0.59 to 0.96) and 0.61 (0.48 to 0.76) in the highest versus lowest quartile, respectively. The smooth curve fittings suggested a non-linear relationship between total carotenoid intake and the risk of current asthma.Conclusions Higher intake of a-carotene, β-carotene, β-cryptoxanthin, lycopene, lutein with zeaxanthin and total carotenoid were associated with lower odds of having current asthma in the US adults. This is a cross-sectional study and no causal relationship can be drawn, so caution is needed to interpret the results.